Interatrial Dyssynchrony May Contribute to Heart Failure Symptoms in Patients with Preserved Ejection Fraction. Issue 11 (1st March 2015) - Sanchis, Laura; Vannini, Luca; Gabrielli, Luigi; Duchateau, Nicolas; Falces, Carles; Andrea, Rut; Bijnens, Bart; Sitges, Marta
Abstract : Purpose: Heart failure (HF) with preserved ejection fraction (HFPEF) is the most prevalent type of HF in nonhospitalized patients, but its pathophysiology remains poorly understood. The aim of our study was to assess the existence of interatrial dyssynchrony (IAD), a potentially treatable condition, in the development of HF symptoms. Methods: Consecutive patients with new onset of shortening of breath, referred for suspected HF, were screened. In all cases, a transthoracic echocardiography, ECG, and determination of plasma BNP level were performed at initial consultation. Patients were diagnosed according to current guidelines. Patients with HF and reduced ejection fraction were excluded. Later, the time from P‐wave onset on the ECG to peak negative strain (atrial contraction) was determined using speckle tracking echocardiography; the time difference between both atria (ms) was used as an index of IAD. Results: Sixty‐six patients were included. Mean age was 74 ± 8 years (74% female, 77% hypertensive). HFPEF patients (n = 32) showed an increased IAD as compared to subjects with non‐HF (n = 34; interatrial time difference 72.7 ± 27 vs. 28 ± 7 ms, P < 0.001). IAD showed a significant correlation with BNP levels, diastolic pattern, and echocardiographic parameters indicative of elevated LV filling pressures. LA function assessed by LA strain rate was not significantly different between HPPEF patients with and without IAD > 60 ms. Conclusions: We showed that IAD was present at initial stages of symptomatic HFPEF. It might be an important mechanism involved in the development of symptoms in HFPEF and a potential target amenable to be treated with device therapy.